2019
DOI: 10.1159/000503559
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Response Improves Overall Survival in Patients with Refractory Ascites: A Meta-Analysis

Abstract: Background and Aims: Refractory ascites represents a significant complication of decompensated cirrhosis, associated with increased mortality rates. The aim of this meta-analysis was to evaluate whether response to treatment with tolvaptan is associated with improved overall survival in cirrhotic patients with refractory ascites. Methods: Medline, Scopus, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, and Google Scholar databases were systematically searched from inception to April 11, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
22
1
1
Order By: Relevance
“…Early meta studies for Vaptan drugs (including Tolvaptan, Satavaptan and Lixivaptan) reported that Vaptan drugs was not associated with prolonged survival in patients with cirrhosis [11][12]. In contrast, a recent meta analysis based on retrospective studies showed that Tolvaptan significantly improves overall survival in patients with cirrhosis and refractory ascites, but this paper has not a high level of evidence [13]. Due to the good efficacy and safety of 7.5 mg Tolvaptan demonstrated in this study, more RCT studies to study Tolvaptan and survival rates in patients with cirrhotic ascites should be performed to support the prognostic role of tolvaptan.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Early meta studies for Vaptan drugs (including Tolvaptan, Satavaptan and Lixivaptan) reported that Vaptan drugs was not associated with prolonged survival in patients with cirrhosis [11][12]. In contrast, a recent meta analysis based on retrospective studies showed that Tolvaptan significantly improves overall survival in patients with cirrhosis and refractory ascites, but this paper has not a high level of evidence [13]. Due to the good efficacy and safety of 7.5 mg Tolvaptan demonstrated in this study, more RCT studies to study Tolvaptan and survival rates in patients with cirrhotic ascites should be performed to support the prognostic role of tolvaptan.…”
Section: Discussionmentioning
confidence: 81%
“…The complications caused by Tolvaptan also receive much attention, apart from the good curative effect. Existing RCT researches report the daily application of low-dose Tolvaptan (7.5 mg or 15 mg) promotes 6-month survival rate of patients with cirrhotic ascites [21], and a latest meta analysis also reported that Tolvaptan could significantly improve overall survival [13]. However, the concrete complications in the use process are not verified by lots of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the good curative effect, complications caused by torvatan are also of great concern. Existing RCT researches report the daily application of low-dose Tolvaptan (7.5mg or 15mg) promotes 6-month survival rate of patients with cirrhotic ascites [21], and a latest meta analysis also reported that Tolvaptan could signi cantly improve overall survival rate [13]. However, the concrete complications in the use have not been con rmed by a large number of data.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are only a few meta-analyses for vaptans drugs (including Tolvaptan, Satavaptan and Lixivaptan), and few results on Tolvaptan, not to mention a comprehensive analysis on the e cacy and safety of Tolvaptan [11,12]. A recent meta analysis for retrospective cohort studies of Tolvaptan reported total survival after application, but no detailed data were available on treatment outcomes and complications [13]. Moreover, we found a meta analysis for Tolvaptan (in Chinese) [14], but most (5/8) of the studies included were single-center clinical trials published in Chinese journals.…”
Section: Introductionmentioning
confidence: 99%